Characteristic grain-size component - a useful process-related parameter for grain-size analysis of lacustrine clastics? - Lu, Yin; Fang, Xiaomin; Friedrich, Oliver; Song, Chunhui (Quaternary international, 2018)
Lacustrine sediments are important archives for paleoclimate reconstructions. The application of grain-size analysis as palaeoclimatic proxy in lacustrine clastics is valuable but also difficult because the typical polymodal grain-size distribution in these clastics. To better understand the grain-size distribution of lacustrine clastics and to promote the application of grain size in paleoenvironmental interpretation, this study investigates lacustrine clastics from northern and southern China. The grain-size distribution of these sediments was decomposed by log-normal distribution function fitting method. Based on the results, and drawing upon the concept of paleomagnetic demagnetization and “Characteristic Remnant Magnetization” from paleomagnetism, a conceptual system has been established and defined for grain-size distribution analysis. The system is composed of four components: (I) Characteristic Grain Size Component (ChGSC), (II) Affiliated Grain Size Component, (III) Meaningful Grain Size Component, and (IV) Combination Feature of Grain Size Components (CFGSCs). Based on the proposed system, ChGSC and CFGSCs were used to detect the grain-size distribution of clastics from the different lake zones investigated. Our results show the number, modal size, and percentage of ChGSC(s) in grain-size distributions are sensitive to changes in the lacustrine environment. The ChGSC(s) mirrors the dominant depositional process and hydrodynamic conditions. The modal size of ChGSC(s) is more sensitive to hydrological conditions than the widely used mean grain-size approach. Thus, the ChGSC(s) provide a useful process-related parameter for paleoenvironmental reconstructions. To test this promising application, we applied this approach to a deep drill core from the Qaidam Basin in the northeastern Tibetan Plateau.
Available online 22 September 2017
Gesehen am 18.07.2019